Entomological study of Anopheles vector bionomics and persistent malaria transmission at National Malaria Control Program Sentinel sites in the Democratic Republic of the Congo - Basosila, Narcisse; Ngbolua, Koto-Te-Nyiwa; Mbembo, Blaise; Masengo, Colette Ashande; Agossa, Fiacre; Zanga, Josué; Mulenda, Basimike; Ulrich, Seth; Nagahuedi, Jonas; Mukomena, Eric (Orapuh Journal, 2024)
Introduction In the Democratic Republic of the Congo, the malaria transmission landscape is influenced by diverse bioclimatic conditions, leading to varied transmission patterns across the country. Purpose The primary objective of this study was to investigate the bionomics of malaria vectors across 22 NMCP sentinel sites. By analyzing the different malaria transmission facies, we aimed to provide detailed insights into vector behavior and abundance to inform more effective malaria control strategies. Methods Mosquitoes were captured at 22 sentinel sites, with sampling conducted in 20 randomly selected households per site. These households were divided into two groups: ten utilized human bait traps, and the remaining ten employed pyrethrum spray catches. The captures were performed over five consecutive nights every six months. A total of 1,723 Anopheles mosquitoes were collected for analysis. Results The study identified five Anopheles species, with Anopheles gambiae s.l. being the most abundant and primary vector, representing 75% of the total captures. The other species included An. funestus group (15%), An. paludis (12%), An. coustani (0.3%), and An. nili (0.2%). Behavioral observations revealed that An. gambiae s.l. is active both indoors and outdoors, with peak biting occurring from 9 p.m. to 4 a.m., and an average biting density of 12 bites per person per night. 13209 mosquitoes (i.e., 88.5%) were captured using the HLC method, while, among the 1,723 mosquitoes captured using the PSC method, 51% were blood-fed, 24% were semi-gravid, 18% were gravid, and 7% were fasting. An. gambiae s.l. was found to be present year-round, contributing to continuous malaria transmission. Conclusion This study provides crucial data on the prevalence and behavior of malaria vectors, particularly emphasizing the role of Anopheles gambiae s.l. as the primary vector in malaria transmission. The findings highlight significant differences in bite rates among species and the year-round activity of An. gambiae s.l., underscoring the need for targeted vector control measures. The data will be used to refine and implement effective vector control strategies, such as long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS), to reduce malaria transmission and mortality rates at NMCP sentinel sites.